Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Terhadap Hasil Belajar IPA Siswa Kelas V SDN 27 Limau Asam - Yuris Nasri; Firman; Desyandri (Universitas PGRI Adi Buana Surabaya, 2021)
This study was made to see the effect of contextual teaching and learning (CTL) learning models on learning outcomes of class V students. This type of research is experimental research with a design